The Effect Of Using Two Strategies for Individual and Team Work On Learning Artistic Performance In 5000m Walking Event - al-Mashhadan, Abdullah; Hussein, Munther (Journal of Physical Education, 2023)
The research tackled applying two strategies of learning; the first strategy is individual work. In this strategy Self – Checked learning style was used. While in the other strategy was team work in which cooperative learning was used.The aims of the research were:Identifying the effect of cooperative learning on learning and developing artistic performance in 5000m walking event.Identifying the effect of self – checked learning on learning and developing artistic performance in 5000m walking event.Designing a teaching program with both self- checked and cooperative learning styles.The researchers hypothesized the following:There are significant statistical difference between pre and posttests for both experimental groups.There are significant statistical differences in the posttests between the two experimental groups.The researchers used the experimental method on 20 high school students. They were equally divided into two experimental groups. The data was collected and treated using proper statistical operations. The researchers came up with many conclusions that proved that there are significant statistical difference between pre and posttests for both experimental groups in favor of posttests. In addition to that, they concluded that there are significant statistical differences between in the posttests in favor of the self- checked group. The researchers recommend using self – checked style to learn this skills as well as making similar studies using different strategies to develop this sport